Vitamin B3 Provides Neuroprotection via Antioxidative Stress in a Rat Model of Anterior Ischemic Optic Neuropathy - Tu-Wen Chen; Po-Ying Wu; Yao-Tseng Wen; Tushar Dnyaneshwar Desai; Chin-Te Huang; Pei-Kang Liu; Rong-Kung Tsai (MDPI AG, 2022)
Supplementing with vitamin B3 has been reported to protect against retinal ganglion cell (RGC) damage events and exhibit multiple neuroprotective properties in a mouse model of optic nerve injury. In this study, a rat model of anterior ischemic optic neuropathy was used to assess the neuroprotective benefits of vitamin B3 (rAION). Vitamin B3 (500 mg/kg/day) or phosphate-buffered saline (PBS) was administered to the rAION-induced rats every day for 28 days. The vitamin B3-treated group had significantly higher first positive and second negative peak (P1-N2) amplitudes of flash visual-evoked potentials and RGC densities than the PBS-treated group (p < 0.05). A terminal deoxynucleotidyl transferase dUTP nick end labeling assay conducted on vitamin B3-treated rats revealed a significant reduction in apoptotic cells (p < 0.05). Superoxide dismutase and thiobarbituric acid reactive substance activity showed that vitamin B3 treatment decreased reactive oxygen species (p < 0.05). Therefore, vitamin B3 supplementation preserves vision in rAION-induced rats by reducing oxidative stress, neuroinflammation, and mitochondrial apoptosis.